Rehabilitation of RC buildings from the late 19th - early 20th centuries - methodological discussion - Esmeralda Paupério (2016)
Reinforced concrete (RC) constructions from the late 19th - early 20th centuries present new challenges associated to their conservation and repair. The specificities involved in the conservation/rehabilitation of historical and heritage RC constructions require a special approach that must account for several restrictions. Such restrictions are related to the safeguarding of the heritages cultural value, significance and authenticity that have to be weighed against safety and durability requirements, as well as against duration and budget constraints of the intervention. For the case of late 19th - early 20th centuries RC constructions, such issues are more complex since materials have evolved and construction techniques of that era cannot be replicated. Some issues that are raised when dealing with the conservation/rehabilitation of these constructions are addressed herein based on a case study. A methodological approach for the conservation of these constructions is discussed, highlighting challenges that need to be addressed.